Cognitive task analysis-based training in surgery: a meta-analysis - Edwards, Thomas C; Coombs, Alexander W; Szyszka, Bartosz; Logishetty, Kartik; Cobb, Justin P (BJS open, 2021)
Reduced hands-on operating experience has challenged the development of complex decision-making skills for modern surgical trainees. Cognitive task analysis- (CTA-)based training is a methodical solution to extract the intricate cognitive processes of experts and impart this information to novices. Its use has been successful in high-risk industries such as the military and aviation, though its application for learning surgery is more recent. This systematic review aims to synthesize the evidence evaluating the efficacy of CTA-based training to enable surgeons to acquire procedural skills and knowledge. The PRISMA guidelines were followed. Four databases, including MEDLINE, EMBASE, Web of Science and Cochrane CENTRAL, were searched from inception to February 2021. Randomized controlled trials and observational studies evaluating the training effect of CTA-based interventions on novices' procedural knowledge or technical performance were included. Meta-analyses were performed using a random-effects model. The initial search yielded 2205 articles, with 12 meeting the full inclusion criteria. Seven studies used surgical trainees as study subjects, four used medical students and one study used a combination. Surgical trainees enrolled into CTA-based training groups had enhanced procedural knowledge (standardized mean difference (SMD) 1.36 (95 per cent c.i. 0.67 to 2.05), P < 0.001) and superior technical performance (SMD 2.06 (95 per cent c.i. 1.17 to 2.96), P < 0.001) in comparison with groups that used conventional training methods. CTA-based training is an effective way to learn the cognitive skills of a surgical procedure, making it a useful adjunct to current surgical training.